2017
DOI: 10.1371/journal.pone.0177342
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of pneumococcal vaccination strategies for the elderly in Korea

Abstract: BackgroundAlthough the 13-valent pneumococcal conjugate vaccine (PCV13) showed good efficacy against pneumococcal disease in the the CAPiTA trial, the 23-valent pneumococcal polysaccharide vaccination (PPSV23) program has been ongoing for older adults aged ≥ 65 years in Korea since May of 2013. This study aimed to evaluate the cost-effectiveness of the current vaccination strategy (a single-dose PPSV23 vaccination) compared to a single-dose PCV13 vaccination and sequential PCV13-PPSV23 vaccinations in the elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Considering significantly high disease burden in the elderly, Korean government have subsidized influenza and pneumococcal vaccines for the old adults aged ≥65 years since 1997 and 2013 years, respectively. [ 13 , 14 ] As for the pneumococcal national immunization program (NIP), free 23-valent pneumococcal polysaccharide vaccine (PPV23) vaccine has been provided for all people aged ≥65 years with a target coverage of 60%. [ 13 ] As of 2016, the coverage rates of influenza vaccine and PPV23 were estimated to be about 80% and 60%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering significantly high disease burden in the elderly, Korean government have subsidized influenza and pneumococcal vaccines for the old adults aged ≥65 years since 1997 and 2013 years, respectively. [ 13 , 14 ] As for the pneumococcal national immunization program (NIP), free 23-valent pneumococcal polysaccharide vaccine (PPV23) vaccine has been provided for all people aged ≥65 years with a target coverage of 60%. [ 13 ] As of 2016, the coverage rates of influenza vaccine and PPV23 were estimated to be about 80% and 60%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] As for the pneumococcal national immunization program (NIP), free 23-valent pneumococcal polysaccharide vaccine (PPV23) vaccine has been provided for all people aged ≥65 years with a target coverage of 60%. [ 13 ] As of 2016, the coverage rates of influenza vaccine and PPV23 were estimated to be about 80% and 60%, respectively. [ 13 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), comparator (PPSV23 or no vaccine), seroepidemiology and treatment cost. For example, four studies found vaccination with PCV13 to be cost-effective compared to vaccination with PPSV23 [61,70,72,73], and two studies found vaccination with PCV13 to be cost-effective compared to no vaccination [20,72]. In contrast to this, three studies found vaccination with PCV13 in sequence with vaccination with PPSV23 to not be cost-effective compared to PPSV23 alone [69,74,75].…”
Section: Sensitivity Analysismentioning
confidence: 95%
“…Mangen et al, however, compared a single dose of PCV13 to no vaccination and results imply that, in that scenario, PCV13 is cost-effective [20]. Other studies in many other countries show similar results, although the vaccination strategies are diverse [69][70][71][72]. It must be noted that these studies are diverse in the population to be vaccinated, vaccination strategies used (sequential use of PCV13->PPSV23, PCV13, revaccination, etc.…”
Section: Sensitivity Analysismentioning
confidence: 99%